Swimming performance of the freshwater neotropical fish: Pimelodus maculatus Lacepède, 1803 - Santos,HA. (2008)
The present study used fixed and increasing velocity tests in an experimental apparatus based on Brett's respirometer to examine prolonged and sustained speeds of the "mandi-amarelo", Pimelodus maculatus. When comparing the curves of critical speed versus total length between the mandi and the sockeye salmon Oncorhynchus nerka, it is observed that for an equal total length, the mandi presents a greater speed, probably due to water temperature differences. The sustained speed for the species was estimated in 5 lengths per second and the percentage of fatigued fish within time in a certain velocity was established. The data raised for the mandi represents an important contribution to the improvement of the handling of the species, providing guidance and criteria for designing several structures, such as fishways, fish screens and guidance systems.